DIAGNOSIS AND TREATMENT OF A PERITONEOPERICARDIAL HERNIA IN AN ADULT DOG: A CASE REPORT - SILVA, L. G.; COSTA, R. C.; FACIN, A. C.; MORAES, P. C.; BRAZ, J. B.; CAMPLESI, A. C.; CAMACHO, A. A. (Ars Veterinaria, 2020)
Peritoneopericardial diaphragmatic hernia is a common congenital pericardial anomaly in dogs and cats, characterized by a communication between the abdomen and the pericardial sac. Animals may be asymptomatic or show nonspecific clinical signs related to the gastrointestinal and cardiorespiratory systems. In this report, we present a case of a 3-year-old female Schnauzer, weighing 7,7 kg, with a history of easy fatigue and cyanosis triggered by stress. The diagnosis of peritoneopericardial diaphragmatic hernia was confirmed through echocardiography and simple and contrast radiography findings that showed the presence of hepatic lobes in the pericardial sac. The animal underwent supra-umbilical celiotomy to correct the hernia and subsequently presented immediate improvement of clinical signs.